Household electrical and electronic waste management practice evaluation in Shah Alam, Malaysia - Ahmad Kalana, Junaidah (2012)
The shorter lifespan of electrical and electronic equipment has contributed to the generation of electrical and electronic waste. From year 2007 to 2010, the total number of electrical and electronic waste that is generated in Shah Alam has increased from 5,323 metric tonnes to 21,205 metric tonnes. The lack of proper facilities for electrical and electronic waste disposal has resulted problem in electrical and electronic waste management from households. Therefore, the main objective of this study is to evaluate the current status of electrical and electronic waste management in Shah Alam. The data for this study derived from two main activities, where the first activity is the collection of secondary data from literature reviews and document searches. Meanwhile, the second activity involved the collection of primary data through survey by using questionnaires. The result of the study shows that the disposal route practice by households in Shah Alam is storage in the house, sold as second-hand electrical and electronic equipment, and disposal with other solid waste. The major electrical and electronic equipment that contributes to the generation of electrical and electronic waste in Shah Alam is mobile phones and computers. Besides that, the disposal of electrical and electronic waste by households is rely on the electrical and electronic equipment lifespan and the way they handled the appliances before the time of disposal. Even though, the household's knowledge of electrical and electronic waste has evolved, but most of them do not know how to dispose the electrical and electronic waste properly. Hence, this study concluded that electrical and electronic waste management in Shah Alam from households not yet established, and study on the proper electrical and electronic waste disposal is necessary to overcome the negative impact in the future.